Меню

УСЛОВИЕ:
Раскрыть скобки и упростить: (2-V3)^2 - V2(V6-1) + 3V12 Сократить дроби. V - знак корня.

х^2-3
---------------
2V3-2x

y+x-2Vxy
---------------
5Vx-5Vy


РЕШЕНИЕ:

Думаю, как-то так:
(2-√3)²- √2(√6-1) +3√12= 2²-2*2*√3-(√3)² -√2*√6+√2 + 3√12=
= 4- 4√3- 3 - √12+ √2+ 3√12=  1  - 4√3 - 2√3 +√2 + 6√3 = 1 +√2

$$ \frac{ x^{2} -3}{2 \sqrt{3}- 2x } = \frac{(x- \sqrt{3})(x+ \sqrt{3} ) }{2*( \sqrt{3}-x) } = \frac{(x- \sqrt{3})(x+ \sqrt{3} )}{-2(x- \sqrt{3})} =- \frac{x+ \sqrt{3} }{2} $$

$$ \frac{y+x-2 \sqrt{x*y} }{5 \sqrt{x} -5 \sqrt{y} } = \frac{( \sqrt{y}- \sqrt{x} )^{2} }{5( \sqrt{x} - \sqrt{y}) } = \frac{( \sqrt{y} - \sqrt{x}) ^{2} }{-5( \sqrt{y}- \sqrt{x} ) } =- \frac{ \sqrt{y}- \sqrt{x} }{5} $$






Похожие примеры: